Prudent Reflective Equilibrium - Coitinho Silveira, Denis (ETHICS IN PROGRESS, 2023)
The main aim of this paper is to propose the inclusion of the expertise of a prudent agent within the procedure of reflective equilibrium by adding a disposition for identifying reasonable beliefs. This can be seen as the starting point of the method, and would safeguard against the criticism of conservatism and subjectivism. In order to do this, I will begin by analyzing the core characteristics of the method and its main weaknesses. I will then investigate the characteristics of prudence as a disposition for identifying an adequate means for achieving a good end. With this in mind, I will apply prudence to the procedure which is carried out by an agent who deliberates well and can identify reasonable moral beliefs. These beliefs must be justified according to their consistency with ethical principles and with the factual beliefs of relevant scientific theories. Finally, I will argue that this deliberative process is consistent with ethical pluralism and democracy, and can be interpreted as a kind of moral knowledge.